THE IMPACT OF ENVIRONMENTAL FACTORS ON CARDIOVASCULAR HEMODYNAMICS UNDER THE CONDITIONS OF UZBEKISTAN (Eureka Journal of Health Sciences & Medical Innovation, 2025)
This article discusses cardiovascular diseases that arise under the influence of harmful environmental factors and methods for their prevention.
Keywords: Hemodynamics, arterial pressure, cardiovascular system, peripheral vascular resistance, blood rheology, vascular elasticity, heart failure, hypertension, atherosclerosis, environmental factors, conditions of Uzbekistan.